2014
DOI: 10.1039/c4tb00315b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically strong and stretchable PEG-based supramolecular hydrogel with water-responsive shape-memory property

Abstract: A stretchable and elastic supramolecular hydrogel with water-responsive shape-memory behavior, which can be realized under mild and green conditions, was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 39 publications
(44 reference statements)
0
56
0
Order By: Relevance
“…Most SM&SH hydrogels were thermally activated, but one disadvantage is that the direct heating will lead to temperature rising of the entire material . Other stimulating means such as air, water, and pH can also trigger the shape recovery, but those stimuli are limited in practical applications . In contrast, the remote stimulations such as ultrasound and light are very easy to achieve local focus and quantitative stimulation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most SM&SH hydrogels were thermally activated, but one disadvantage is that the direct heating will lead to temperature rising of the entire material . Other stimulating means such as air, water, and pH can also trigger the shape recovery, but those stimuli are limited in practical applications . In contrast, the remote stimulations such as ultrasound and light are very easy to achieve local focus and quantitative stimulation .…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Other stimulating means such as air, water, and pH can also trigger the shape recovery, but those stimuli are limited in practical applications. [23][24][25][26] In contrast, the remote stimulations such as ultrasound and light are very easy to achieve local focus and quantitative stimulation. [27,28] Previously we firstly proposed the use of therapeutic ultrasound to trigger the shape memory of a PVA hydrogel containing a small amount of melamine.…”
mentioning
confidence: 99%
“…H-bonded C=O stretching peaks from urea groups appear in the 1620-1690 cm -1 range, those non-bonded appear in the 1690-1715 cm -1 range. 24,37 As a first step in investigating the mechanical performance, strain (γ, Fig. [27][28][29][30] From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 While, in nature and other self-assembly systems, hydrophobic effect can shield the H-bonds from the water and forms a more nonpolar local domain for enhancing the H-bonding interactions, yielding supramolecular hydrogels in water. 23,24 But the synthesis procedures are complicate and time consuming. Recent studies showed that chain-extension of the ureidopyrimidinone (UPy) end-functionalized PEG to multi-block architecture can greatly enhance the mechanical performance of the obtained copolymers compared with the telechelic analogues having nearly identical composition.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure and Movie S4 of the Supporting Information, the hydrogel can recover to its original shape in 20 min. The mechanism of the water‐induced shape recovery is assumed as follows: when the dehydrated hydrogel is immersed in water, water molecules will diffuse into the hydrogel network and act as plasticizers, which will decrease the interactive forces among the tangled polymer chains, and induce the shape recovery process …”
Section: Resultsmentioning
confidence: 99%